PERAN FILSAFAT PENDIDIKAN DALAM MENENTUKAN KARAKTER DAN TIPE GURU DI ERA MODERN - Rahmawati; Ismail (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study examines the role of educational philosophy in shaping the character and type of teachers in the modern era facing technological and social challenges. Using the literature study method, it was found that educational philosophy, through schools such as idealism and pragmatism, provides guidance for integrating moral values, professionalism, and adaptive abilities in the role of teachers. The results of the study highlight the importance of teachers as technology facilitators and motivators who are able to build student character. Teachers are not only expected to master the material, but also to be moral role models that are relevant to changing times. However, challenges such as technological gaps and changes in cultural values ​​require solutions in the form of continuous training and adaptive learning. With this approach, educational philosophy remains relevant in supporting educational transformation in the modern era.